2021
DOI: 10.1159/000516765
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Severity of Cutaneous Manifestations in IgA Vasculitis Is Associated with Development of IgA Vasculitis Nephritis in Children

Abstract: <b><i>Background/Objective:</i></b> The purpose of this study was to evaluate the prevalence and severity of skin involvement in children with IgA vasculitis (IgAV) and its relationship with clinical and biochemical parameters and the risk of developing IgA vasculitis nephritis (IgAVN), the only cause of long-term morbidity and the main prognostic factor in IgAV patients. <b><i>Methods:</i></b> This national multicenter retrospective study included 611 patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Such skin alterations developed in 2-3% of patients with IgAV and recently it was shown that with increasing severity and duration of cutaneous manifestations in IgAV, the risk of developing IgAVN increases, making the prognosis worse with a greater likelihood to have required more aggressive treatment. 32 Furthermore, it was found that the presence of ulcerations and necroses, persistent purpura (more than 1 month) and age were significant predictors of IgAVN, while persistent purpura, male gender and age were predictors of persistent IgAVN (hematuria and/or proteinuria more than 3 months). 32 Musculoskeletal manifestations are the second most common feature and up to 70-90% of patients will have arthralgia or arthritis.…”
Section: Igavn and Other Clinical Manifestationsmentioning
confidence: 93%
See 2 more Smart Citations
“…Such skin alterations developed in 2-3% of patients with IgAV and recently it was shown that with increasing severity and duration of cutaneous manifestations in IgAV, the risk of developing IgAVN increases, making the prognosis worse with a greater likelihood to have required more aggressive treatment. 32 Furthermore, it was found that the presence of ulcerations and necroses, persistent purpura (more than 1 month) and age were significant predictors of IgAVN, while persistent purpura, male gender and age were predictors of persistent IgAVN (hematuria and/or proteinuria more than 3 months). 32 Musculoskeletal manifestations are the second most common feature and up to 70-90% of patients will have arthralgia or arthritis.…”
Section: Igavn and Other Clinical Manifestationsmentioning
confidence: 93%
“…32 Furthermore, it was found that the presence of ulcerations and necroses, persistent purpura (more than 1 month) and age were significant predictors of IgAVN, while persistent purpura, male gender and age were predictors of persistent IgAVN (hematuria and/or proteinuria more than 3 months). 32 Musculoskeletal manifestations are the second most common feature and up to 70-90% of patients will have arthralgia or arthritis. 31 The affected joints have painful ranges of movement due to periarticular swelling, but the characteristic findings of warmth, erythema and effusion are often absent.…”
Section: Igavn and Other Clinical Manifestationsmentioning
confidence: 93%
See 1 more Smart Citation
“…It is proposed to follow-up patients with IgAV for at least 6–12 months even if the initial blood pressure measurements and urinalysis are normal ( 74 ), measuring regularly blood pressure and performing urinalyses to detect presence of haematuria, and quantification of albuminuria and/or proteinuria. Bearing in mind that recently published research has indicated that a certain group of patients (such as older children with the onset of gastrointestinal symptoms before other IgAV symptoms and severe GI form of IgAV, as well as those who develop ulcerations and necroses and persistent purpura) may be at higher risk for the later development of nephritis, the question arises whether some children should be monitored longer than recommended ( 54 , 59 ).…”
Section: New Insights In the Follow-up Of Patients With Igavmentioning
confidence: 99%
“…Furthermore, hemorrhagic bullae, ulcerations and necrotic lesions can be seen in the most severe cases. Recently, several papers have been published on severe skin changes in patients with IgAV, questioning whether these changes are associated with more severe disease, persistent sequelae, and discussing how to treat patients with such manifestations (52)(53)(54). The results of these studies are not uniform, and according to some authors the presence of ulcerations and necroses, persistent purpura (≥1 month) and older age were significant predictors of IgAVN.…”
Section: New Insights In the Clinical Presentations Of Igavmentioning
confidence: 99%